Shock and awe [videorecording (DVD)] - Reiner, Rob; Marsden, James, 1973-; Harrelson, Woody; Biel, Jessica, 1982-; Jovovich, Milla; Jones, Tommy Lee, 1946- (Vertical Entertainment, 2018)
The untold true story of an intrepid team of four reporters of Knight Ridder who dared to ask the questions their colleagues did not in the aftermath of the terrorist attacks on September 11, 2001.